Targeted metagenomics unveils the molecular basis for adaptive evolution of enzymes to their environment - Suenaga, Hikaru (Frontiers in Microbiology, 2015)
Microorganisms have a wonderful ability to adapt rapidly to new or altered environmental conditions. Enzymes are the basis of metabolism in all living organisms and therefore enzyme adaptation plays a crucial role in the adaptation of microorganisms. Comparisons of homology and parallel beneficial mutations in an enzyme family provide valuable hints of how an enzyme adapted to an ecological system; consequently, a series of enzyme collections is required to investigate enzyme evolution. Targeted metagenomics is a promising tool for the construction of enzyme pools and for studying the adaptive evolution of enzymes. This perspective article presents a summary of targeted metagenomic approaches useful for this purpose.